Effects of Fineness and Chemical Composition of Blast Furnace Slag on Properties of Alkali-Activated Binder - Abeer M. Humad (Materials, 2019)
The effects of fines and chemical composition of three types of ground granulated blast furnace slag (GGBFS) on various concrete properties were studied. Those studied were alkali activated by liquid sodium silicate (SS) and sodium carbonate (SC). Flowability, setting times, compressive strength, efflorescence, and carbonation resistance and shrinkage were tested. The chemical composition and microstructure of the solidified matrixes were studied by X-ray diffraction (XRD), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM) coupled with EDX analyser. The results showed that the particle size distribution of the slags and the activator type had significantly stronger effects on all measured properties than their chemical composition. The highest compressive strength values were obtained for the finest slag, which having also the lowest MgO content. SC-activated mortar produced nearly the same compressive strength values independently of the used slag. The most intensive efflorescence and the lowest carbonation resistance developed on mortars based on slag containing 12% of MgO and the lowest fineness. The slag with the highest specific surface area and the lowest MgO content developed a homogenous microstructure, highest reaction temperature and lowest drying shrinkage. Thermogravimetric analysis indicated the presence of C-(A)-S-H, hydrotalcite HT, and carbonate like-phases in all studied mortars.